Directive Speech Acts in Islamic Academic Discourse: Can Pragmatic Analysis Reveal Islamic-Specific Politeness Patterns? - Heru Susanto; Andayani Andayani; Atikah Anindyarini (Jurnal Pendidikan Islam, 2026)
In global higher education, classroom interaction has become a central concern in understanding how language practices shape participation, authority, and learning effectiveness. Directive speech acts, as a key component of academic discourse, play a crucial role in managing interaction and facilitating instructional processes across diverse cultural and institutional settings. This study aims to examine the usage and functions of directive speech acts among students in an Islamic higher education learning environment. Employing a qualitative case study approach, the research analyzed recorded classroom interactions involving 48 students from the Indonesian Language Tadris Study Program at Sultan Muhammad Syafiuddin Sambas University (UNISSAS), West Kalimantan. Data were collected through classroom observation and documentation and analyzed using the Miles and Huberman interactive model, which includes data reduction, data display, and conclusion drawing. The results identified 78 instances of directive speech acts classified into six functional categories: requests (26.92%), commands (23.08%), invitations (15.38%), prohibitions (14.10%), suggestions (11.54%), and advice (8.97%). Requests and commands emerged as the most dominant forms, reflecting the instructional orientation of classroom discourse and students’ efforts to ensure participation and mutual understanding. In conclusion, directive speech acts function not only as pragmatic tools but also as ethical communicative strategies in Islamic academic contexts. The study implies that strengthening pragmatic awareness in Islamic education can promote effective, respectful, and harmonious classroom communication aligned with Islamic values.